2003
DOI: 10.2519/jospt.2003.33.4.204
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Landing Forces in Children: The Effect of Instructions

Abstract: Study Design: Randomized controlled experimental design. Objectives: To examine the effects of verbal instructions related to control of joint kinematics and auditory feedback on lowering the vertical peak ground reaction forces associated with landing from a jump in children. Background: The majority of children's injuries are associated with activities that involve jumping and landing. Instructions related to joint motion may assist children in decreasing landing forces and thus reduce the chances of sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 13 publications
7
50
0
Order By: Relevance
“…(Winstein, 1991) Traditionally, feedback has been a type of training technique used to provide participants with a knowledge of results, which is the outcome of the movement, or knowledge of performance, which is a description of the movement quality. (Kernodle and Carlton, 1992) Feedback can be delivered using self-analysis techniques by the same individual receiving the feedback (Oñate et al, 2005), or feedback can be provided via an analysis provided by an expert (Cronin et al, 2008;Prapavessis et al, 2003). Expert provided feedback may rely on oral correction or instruction of different movements.…”
Section: Discussionmentioning
confidence: 99%
“…(Winstein, 1991) Traditionally, feedback has been a type of training technique used to provide participants with a knowledge of results, which is the outcome of the movement, or knowledge of performance, which is a description of the movement quality. (Kernodle and Carlton, 1992) Feedback can be delivered using self-analysis techniques by the same individual receiving the feedback (Oñate et al, 2005), or feedback can be provided via an analysis provided by an expert (Cronin et al, 2008;Prapavessis et al, 2003). Expert provided feedback may rely on oral correction or instruction of different movements.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is most likely that these reductions were too small to be of any clinical significance in reducing knee injury risk. Several technique-training studies have demonstrated temporary reductions in vertical ground reaction forces (13%-27%) using verbal instruction with 6,12,24,27,28 or without 5,23,30,31 feedback. Completion of a 1-week home-based training program did not result in significant changes in peak knee adductor moment or abduction angle compared to baseline values, thus did not result in long-term changes in frontal plane variables.…”
Section: Discussionmentioning
confidence: 99%
“…These additional instructions to reduce landing forces at the time of testing most likely led to their long-term findings. Prapavessis et al 31 performed a long-term retention test 3 months after their intervention. Unfortunately, their jump-landing instructions did not result in long-term reductions in ground reaction forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators [42][43][44][45][46] have shown that providing adults and youths with oral cues on which to focus can acutely modify lower extremity movement patterns during a jump-landing task. In agreement with these findings, the youth athletes in our study who completed the IPP achieved relatively more improvement in jump-landing technique than the athletes who completed the other 2 warm-up programs.…”
Section: Double-legged Heel Raise: 20 Repetitionsmentioning
confidence: 99%